Manajemen Bakat di Sektor Pariwisata dan Perhotelan: Sudut Pandang Konseptual - Haryanto, Eko; Kiswantoro, Amin; Rohman, Nur; Maulana, Rizky; Makiya, Kiki Rizki; Noviati, Fitria (Universitas Pendidikan Ganesha, 2023)
This research provides a context analysis of talent in the tourism and hospitality industry. The industry is a vital sector for many economies with its highly service-oriented nature, an important strategy to ensure effective recruitment and retention of employees with relevant skills and knowledge. The aim of this research is to provide an overview to politicians and stakeholders regarding the processing of various ideologies, perspectives and interventions that improve management talent. The method used is a qualitative method with the type of literature review or literary study. Critical analysis is made of existing print and online materials. The novelty findings of this article offer new insights into talent management in the tourism and hospitality industry. The results reveal two main research themes; First, there is a positive correlation between the talent management strategy adopted and the creation of global competitiveness. second, institutional culture influences the implementation of planning strategies, which in turn influences talent management.